Biologic therapy in supra-aortic Takayasu arteritis can improve symptoms of cerebral ischaemia without surgical intervention. (29th April 2020) - Porter, Andrew; Youngstein, Taryn; Tombetti, Enrico; Mason, Justin C
Abstract: Objectives: Takayasu arteritis commonly results in severe arterial injury with stenoses, occlusions and occasionally aneurysms. Arterial disease may compromise organ blood flow and result in significant cardiovascular morbidity and premature mortality. Involvement of the supra-aortic arteries is common, and in its most severe form may compromise cerebral blood supply, resulting in signs of cerebral ischaemia including visual impairment, dysphasia, transient hemiparesis, loss of consciousness and stroke. In addition to combination immunosuppression, the management paradigm for symptomatic cerebral ischaemia includes revascularization. The invasive nature of this surgery, the risk of complications and the relatively high rate of re-stenosis is of concern to patients and their physicians alike. The aim of this study was to determine whether combined immunosuppression with early escalation to biologic therapy improved outcomes and reduced the need for high risk surgical intervention. Methods: A retrospective review of 145 Takayasu arteritis patients attending Imperial College Healthcare between 2010–2018 was conducted to identify those with cerebral ischaemia secondary to supra-aortic disease and to analyse their treatment and outcomes. Results: Eight patients (5.5%) were identified. Seven patients received long-term combined immunosuppressive therapy and six were prescribed biologics. The data revealed a higher than expected comprehensive response to therapy, with significant falls in disease activity, the cerebral ischaemia score and the prednisolone dose required, over a median follow-up of 37 months. Serial imaging analysis detected no arterial disease progression after the initiation of optimal therapy. Only one patient required surgical intervention for persistent neurological symptoms. Conclusion: Early use of biologic therapy in those with supra-aortic Takayasu arteritis presenting with cerebral ischaemia may reduce the numbers of patients requiring surgical intervention and improve outcomes.